Biopolitical laboratory and the genetic modification of the psyche - Janeš, Luka (Array, 2019)
In the era marked by the universal fascination and the naïve, “mesianistic” belief in the salvationary and the utilitarian “demiurgistic” grasp of a genetic engineering and subsequent modification of the causal-natural cycle, arises an inevitable question of the critical consideration of the phenomena of the psyche in the context of the given metamorphosation. Namely, in this article, the author will observe the human psyche as a kind of relational, dialectical tangent that vitally connects the mind and body of an individual, both in the cognitive and the material sense. It will also be argued that genetic engineering of it does not require research laboratories in which scientists “play” with mental genes, instead of which the sufficient tools are the ones of “biopolitical laboratory”, with an instrumental methodology marked by the marketing pressures and the media lobotomization, biopolitical manipulation, abiotic education and excessive use of medicaments in the psychiatric treatment of mental disorders. The above-stated questions dominate the discourse of the article, introducing the orientative knowledge and bioprotectionistic1 teleology of discipline of integrative-bioethical paradigm as a potential scientific and social platform for rethinking and pragmatically overcoming the issues presented in the discourse of the article.